A Novel Approach to Digital Image Security: Merging Cryptography and Steganography via LSB+TWO Technique - Nur Budi Nugraha; Yaqutina Marjani Santosa (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
The increasingly rapid development of the digital era has resulted in information security becoming a crucial aspect in communication and data exchange. Digital images as a medium commonly used to store and transmit information are the main target in developing data security techniques. As the volume and sensitivity of information exchanged via digital images increases, the need for more sophisticated security mechanisms becomes increasingly pressing. This research combines cryptography and steganography using the LSB+TWO method. We integrate 256-bit AES in CBC mode for initial encryption, followed by improved LSB steganography techniques and a modified TWO algorithm. This method was tested on various datasets consisting of 1000 digital images with various resolutions. The results demonstrate significant improvements in the security and robustness of steganalysis compared to conventional methods, while maintaining high visual quality measured by PSNR and competitive embedding capacity. This research makes a significant contribution to the field of digital information security and paves the way for further development in image-based data protection techniques.